2022
DOI: 10.1002/iid3.704
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy for Immunoglobulin E‐mediated cow's milk allergy in children: A systematic review and meta analysis

Abstract: Backgound: Cow's milk allergy (CMA) is the most common allergy in infants that decreases the quality of life of patients and their families. Standard treatment for CMA is the strict avoidance of milk; new treatment strategies such as oral immunotherapy (OIT) have been sought for patients with CMA.We aimed to assess the clinical efficacy and safety of OIT in the treatment of children with immunoglobulin E-mediated CMA (IMCMA). Methods:We searched all randomized controlled trials in which OIT is used to treat ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…They have all captured different studies in their inclusion criteria, so they have differing numbers of studies and different estimates for efficacy and harm. For example, for milk OIT efficacy meta-analyses, one review 22 Efficacy must be balanced with the rate of allergic events.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They have all captured different studies in their inclusion criteria, so they have differing numbers of studies and different estimates for efficacy and harm. For example, for milk OIT efficacy meta-analyses, one review 22 Efficacy must be balanced with the rate of allergic events.…”
Section: Discussionmentioning
confidence: 99%
“…They have all captured different studies in their inclusion criteria, so they have differing numbers of studies and different estimates for efficacy and harm. For example, for milk OIT efficacy meta‐analyses, one review 22 found a RR of 7.35 (2.82–19.13) from 11 studies, a second review 20 found a RR of 12.3, 95% CI: 5.9 to 26.0 from 13 studies, and the third 21 RR 5.7 (1.9–16.7) from 8 studies. These differing estimates are confusing for patients, clinicians and for informing guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations